Kinerja Aparatur Desa Terhadap Peningkatan Pelayanan Publik Berbasis Digital di Desa Abbokongang Kecamatan Kulo - Dian Safitri; Andi Uceng; Sundari Sundari; Adam Latif (Policy, Law and Political Research Center, 2026)
This study aims to analyze the influence of village apparatus performance on the improvement of digital-based public services in Abbokongang Village, Kulo District. The low quality of digital services, limited technological competence of village officials, and minimal assistance provided to the community constitute the background of this study. This research employs a quantitative method with a descriptive approach. The respondents consisted of 52 residents of Abbokongang Village selected through purposive sampling. Data were collected through observation, questionnaires, and interviews, while data analysis was conducted using simple linear regression with the assistance of IBM SPSS Statistics 26. The results indicate that the performance of village apparatus has a significant effect on digital-based public services, as evidenced by an F-value of 165.275 and a significance level of 0.000. The coefficient of determination of 0.768 indicates that the performance of village apparatus contributes 76.8% to the improvement of digital-based public services.